Prenatal Yoga Socialization for Gentle Birth for Pregnant Women by Health Faculty Unjani Yogyakarta Community Service Program - Ratih Kumoro Jati; Dian Puspitasari; Lily Zulaikhah (Peneliti Teknologi Teknik Indonesia, 2022)
Pregnancy and childbirth are natural to women but bring about physical and psychological changes. A woman's body will undergo various changes that affect her health during pregnancy. One way to maintain health during pregnancy, both physical and mental health, is to do yoga. Yoga can aid in a comfortable soft birth delivery because pregnant women are taught to move the pelvis and relax to reduce stress during the birth. Practicing yoga and meditation regularly during pregnancy will build harmonious communication between prospective mothers and their babies, provide an unforgettable experience to enjoy every second full of miracles from the human birth process, and make the pregnancy a memorable moment. Covid-19 has caused some pregnant women to worry about attending yoga classes because of the risk of getting the virus. Therefore, the community service held prenatal yoga virtually for 30 pregnant women using Zoom meetings to facilitate yoga practice intended to reduce discomfort due to the pregnancy, get acquainted with other participants, and exchange information about pregnancy.